Hepatic Effects of Chronic Occupational Cement Dust Exposure: Enzyme Profile Analysis (Bangladesh Journal of Medical Science, 2026)
Background Occupational cement dust exposure poses significant health risks, with recent evidence suggesting potential impacts on liver function, particularly in developing countries with expanding cement industries. Objectives This study aimed to evaluate the effect of chronic occupational cement dust exposure on liver function among male adults working in a cement factory in Bangladesh, assessing serum liver enzyme levels as biomarkers of hepatic stress. Methods A cross-sectional study was conducted from September 2017 to August 2018 at Dhaka Medical College, Dhaka, and Ninety-two healthy males aged 20- 50 years were enrolled, including 46 workers exposed to cement dust for at least 2 years working in a Munshiganj-based cement mill in Bangladesh and 46 matched controls with no occupational exposure. Liver enzymes, Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic-Oxaloacetic Transaminase (SGOT), and alkaline phosphatase (ALP) were assessed using automated analyzers. Statistical analyses included the Mann-Whitney U test, the Pearson correlation coefficient test, and logistic regression. Result Mean liver enzyme levels (SGPT and SGOT) were significantly reduced while serum ALP increased dramatically in exposed workers compared to controls, with a p-value of